(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the impact of job motivation, personnel competence, and organizational commitment on employee performance in the Tabanan Regency education office. This research was conducted at the Tabanan Regency Education Office on Jl. Palawan, Delod Peken, Kechi. Tabanan, Cab Tabanan, Bali. This population is (PNS) in the Department of Education, Tabanan Province (2022), consisting of a total of 98 people from a total of 98 respondent samples determined by a sampling method using a saturated sample. increase. Data in this study were collected using questionnaires and analyzed using data analysis techniques such as validity, reliability, classical assumptions, multiple regression analysis, coefficient of determination, t-test and F-test. Seen: Job motivation, HR competence, and organizational commitment have a positive and significant impact on employee performance. The magnitude of the independent variable’s effect on employee performance is 65.5%. In light of the investigation, the Tabanan Government Education Department should provide regular professional training to its employees. For example, not being late to the office or being absent most of the time unless it’s an emergency will certainly lead to poor performance.